2010
DOI: 10.1002/app.32963
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of chain entanglement on the glass transition of a hydrophilic polymer

Abstract: In this article, we report an interesting phenomenon of the glass transition temperature (T g ) deviation of a hydrophilic polymer. Polyacrylamide (PAL) samples with different extents of chain entanglement were prepared by spray drying and solution casting. We found that the glass transition temperature increases as the extent of chain entanglement decreases upon the sub-T g annealing. The water content in the PAL matrix is found with no direct correlation to T g . However, the observation of a faster diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…When cast from the 30 vol % methanol/THF solvent mixture, the graft copolymers showed a T g of −3.9 °C that was significantly lower than the T g of those cast from THF (13.6 °C). The significant decrease in T g , which is an effect of the solvent mixture, suggests the increased entanglement 53 of grafted PAUs in the graft copolymer films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When cast from the 30 vol % methanol/THF solvent mixture, the graft copolymers showed a T g of −3.9 °C that was significantly lower than the T g of those cast from THF (13.6 °C). The significant decrease in T g , which is an effect of the solvent mixture, suggests the increased entanglement 53 of grafted PAUs in the graft copolymer films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A much smaller decrease of only 2–5 °C was reported by Bernazzani et al The change of glass transition temperature for PS depended not only on the concentration, but also on the kind of solvent used . The decrease of T g is interpreted in the literature as an enhanced degree of freedom of the bond rotation by a reduction of the entanglements, affecting the chain relaxation process . It can be cohesional entanglements, resulting from local nematic interactions between neighboring chain segments.…”
Section: Properties Of Polymers With Limited Density Of Entanglementsmentioning
confidence: 87%
“…Sometimes an increase of T g is observed for the disentangled polymer instead of a decrease. A hydrophilic polyacrylamide (PAM) prepared by spray drying showed an elevated T g compared to its bulk state . The spray‐dried particles and the bulk PAM were formed in films and annealed at 180 °C (i.e., near, but below T g ) for 2–16 h .…”
Section: Properties Of Polymers With Limited Density Of Entanglementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al found that a hydrophilic polymer polyacrylamide (PAL) presented an increased T g with decreasing chain entanglement and they attributed it to the strong molecular interaction formed between an amino group and a carbonyl group in PAL. 56 However, the PMMA/SMA system differs from the PAL one. It is a hydrophobic one and there is no intermolecular interaction between PMMA and SMA molecular, because the hydrogen bonding only occurs between the polymer and the casting solvents during sample preparation.…”
Section: Glass Transition Temperature and Cohesional Entanglement Of ...mentioning
confidence: 99%